Depression and HIV risk among female sex workers in Nelson Mandela Bay Municipality, South Africa: Results from a respondent-driven sampling study - Rossouw, Johannes (Department of Public Health and Family Medicine, 2020)
Sex workers have a higher risk of acquiring and transmitting HIV as a result of social, structural, biomedical and behavioural factors. Many recent studies have highlighted that sex workers and other key populations experience higher levels of depression compared to the general population. Evidence is also emerging that mental health issues such as depression are related to HIV risk behaviour as well as the social and structural factors that leave sex workers vulnerable to bio-behavioural risks. The study protocol is described in Part A of this mini-dissertation. The study from which these data were derived is discussed in detail. Particular attention is placed on the use of respondent-driven sampling as a probabilistic method to estimate population proportion for hidden populations. The primary outcome, depression, and how it is measured through the Patient Health Questionnaire 9, is discussed in detail. The objective of measuring the prevalence of depression and assessing how it relates to risk factors is noted. The protocol argues that most research on sex workers focuses only on social, structural and bio-behavioural risk factors and rarely includes intrapersonal factors such as mental health. Based on this gap, it is argued that this research will help elucidate how depression, as an intrapersonal factor, relates to HIV risk. The literature review in Part B expands the argument that mental health in general and depression in particular are not given the attention they deserve as there are very few studies that measure mental health variables and even fewer that attempt to make any link between mental health, bio-behavioural risk and social vulnerabilities. The journal article in Part C offers empirical evidence that depression is higher among female sex workers than the general population and that depression is strongly associated with bio-behavioural and social risk factors. The article argues for more integration of mental health in research and programme implementation among sex workers.